(3GdYHGH GdeMjW HeYXe fUhU GdTGaYi hGdCUMGHs - (3GdeRLO , CMeO Hf YeQ Hf eMeO GdSjaj GdeOGOj, Uaj GdOjf,J (B930 (3g` s ((3CMeO Hf MSf Hf Ydi GdJdhGfi s)
(3ChdgG (B:s
(3fGbU GdChd hChd GdehLhO efg bHd HGH GdMOK (B" (3Ydi fLGSI GdeMd , hMce GdjO Mce eZShd HbjJ ajg QGFMg YSQI s
(3BNQgG (B:s
(3NGJeI dh GSdeJ eSJhdOI GdcGaQ aJhVY eY EeQCI KbI hjRhLgG GdbGVi HEPfg hEf cQgJ , hegQgG dg hdGdg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI CNQis
(3YdjgG ebGHdI hJUMjM HGdeSLO GdMQGe HecI GdecQeI SfI (B1257(3g` s
(3hYdi GdfSNI JbjjOGJ cKjQI hGdCHhGH hGdaQhY ajgG HGdMeQI s
(3hYdi GdhQbI GdChdi Jedc SfI (B1162(3g` hYdi GdhQbI GdChdi JQLeJg s
Keywords: (3Gdabg GdTGaYjs